Artistic intentions of Paul Valéry: new paradigm of uniting music and architecture - Antonova, Maryna (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2025)
The relevance of the study. Paul Valéry is a prominent French poet, philosopher, and author of a large number of essays whose work spans the period from the late 19th to the first half of the 20th century. One of the most striking pages of the artist’s work is the creation of a new philosophical paradigm for combining music and architecture. It is noteworthy that the influence of P. Valéry’s works on the above-mentioned topics was widespread among twentieth-century artists, in particular: A. Honegger, A. Gide, A. Perret, J. Merrill, E. Bowers and many others. Therefore, in order to understand the specifics of Paul Valery’s innovative paradigm of combining music and architecture and the reasons for its extraordinary rapid spread in the cultural space of the twentieth century, it seems necessary to study the development and formation of the author’s philosophical thought on the example of individual works. The main objective of the study is to reveal Paul Valéry’s individual philosophical vision concerning the essence of the combination of music and architecture. The research methodology: genre-genetic (to study the wide palette of P. Valéry’s works and areas of his creative interest), structural-analytical (for a deep analysis of the specific structure of P. Valéry’s literary works), comparative (to study the differences and similarities in the embodiment of the idea of combining music and architecture by P. Valéry). Results and conclusions. In such works as the essay «The Paradox of Architecture», the poem «Orpheus», the dialogue «Eupalinos or the Architect» and the melodrama «Amphion», Paul Valéry consistently embodies his vision of art, where architecture and music not only coexist but also interact, creating a harmonious union. Paul Valéry’s original rethinking of the unity of artistic spheres became the basis for the development of a new philosophical paradigm that united different artistic fields into a unique spatial and temporal reality. The core of this reality is the personified image of Orpheus, who embodies not only the connection between music and architecture, but their inseparable unity within the new artistic universe. In fact, Orpheus acts as a guide that harmoniously combines the duration of music with the immobility of architectural forms, embodying P. Valéry’s philosophical reflections on art as a space of creative interaction. The process of building a temple, which is a repeated motif in Valéry’s work, serves as a metaphor for the harmony of the arts. The temple, as a place where music has historically lived and developed, becomes an ideal space for the realization of Paul Valéry’s idea of combining the arts. This process of construction, which unfolds around the figure of the Artist, opens up the possibility of creating a new, common time-space reality for music and architecture. Only while these moments of universal unity last, the laws of a different order apply, where there is nothing superfluous except the act of creating beauty.